One-dimensional simulation of two stroke hydrogen direct injection linear generator free-piston engine - Muhammad Alliff, Rahim (2010)
Developing one-dimensional (1D) simulation of two stroke hydrogen direct injection linear generator free-piston engine (2-stroke H2-DI LGFPE) is a low cost approach and it can avoid errors. A 1D simulation 2-stroke H2-DI LGFPE has been developed using GT-POWER software. The performance parameters of a 2-stroke H2-DI LGFPE have been investigated through various bore and stroke configurations. The performance parameter is also obtained by identifying 2-stroke H2-DI LGFPE at various start of fuel injection (SOF), start of ignition (SOI) and fuel per cycle (FPC). The modeling of 2- stroke H2-DI LGFPE in GT-POWER requires different technique than the conventional engine since the crank slider mechanism is absent. The results from the simulation are compared with Fathallah, 2009, Maher, 2004 and Mikalsen, 2008c. From the analysis, the optimum performance is obtained when bore-stroke (B/S) ratio is 0.86. For the SOF, the optimum performance gain at piston position of 65.17 mm before TDC (bTDC). The optimum time for SOI is when piston position at 66.32 bTDC in order to get a better performance of 2-stroke H2-DI LGFPE. The operation at high engine speed of 6000 RPM, the optimum performance gains at FPC 100 mg which is a rich operation for 2- stroke H2-DI LGFPE simulated. At engine speed within the range of 1000 RPM until 4000 RPM, lean operation should be chosen in order to reduce brake specific fuel consumption (BSFC). However, the lean operation will result in reducing the brake power of the LGFPE.